RESPONSE OF BIRD RICHNESS IN THE PRESENCE OF VISITORS, VEHICLES AND DOGS IN “EL CULEBRON” WETLAND, CHILE - Chávez-Villavicencio, César (2015)
“El Culebron” is a coastal wetland in the region of Coquimbo (Chile). Normally, visitors, pets and vehicles affect wetlands, especially birds, causing nest destruction, death of chicks, and foraging deficiencies, among others. El Culebron receives the pressure of visitors and is affected by the presence of pets accompanied by their owners, stray and feral dogs that latter hunt species of wild bird in packs. To address this problem, it was set as the main objective to determine the response of bird richness in the presence of visitors, vehicles and dogs in general. Between August 2012 and September 2013, counts of birds, visitors, vehicles and dogs were made from fixed points and with double observers. The data were analyzed using a Poisson regression selecting the best model with the Akaike Information Criterion. It was established that bird richness responded negatively to the presence of visitors during the summer, declining 1% for each visitor that came to the wetland. In the winter, the bird richness did not correspond to the studied variables. In no season did the presence of dogs impact bird richness.